Preparation, characterisation and solar photoactivity of titania supported strontium ferrite nanocomposite photocatalyst - Aziz, A.A.; Puma, G.L.; Ibrahim, S.; Saravanan, P. (2013)
Enhanced ferromagnetic and visible light active titanium dioxide (TiO2) photocatalyst was synthesised by depositing a hard ferromagnet strontium ferrite (SrFe12O19) onto TiO2 via an effortless hydrothermal and poly-condensation method. The catalysts were characterised by X-ray diffraction (XRD), transmission electron microscope (TEM), energy dispersive X-ray spectroscopy (EDS), BET surface analysis, vibrating sample magnetometer (VSM), X-ray photon spectroscopy (XPS), Fourier transform infrared spectroscopy (FT-IR) and UV-visible light spectroscopy analysis. The prepared nanocomposite photocatalyst exhibited physically a powerful ferromagnetic property with significant stability against the loss of its magnetic property (coercivity ≈2200 G). The catalyst can be fluidised and recovered by an external magnetic field enhancing separation and mixing efficiency. Furthermore, it resulted in a reduced band gap (≈2.3 eV) which resulted in enhanced visible light absorption compared with unsupported TiO2. The photocatalytic activity was investigated by degrading a recalcitrant phenolic compound, viz., 2, 4-dichlorophenol (2,4-DCP) as model pollutant under different illuminance of daylight. Complete degradation of 2,4-DCP (50 mg/L initial concentration in 0.25 L) was achieved in 120 min (supported photocatalyst) and 180 min (unsupported TiO2) under higher illuminance of sunlight. Likewise under diffused sunlight, 100% degradation of 2,4-DCP was achieved in 240 min for the supported TiO2, while ≥90% degradation could be achieved in 300 min for the unsupported TiO2. The supported nanocomposite was recycled under a permanent magnetic field with a mass recovery of 98% and reused. © 2013 Copyright Taylor and Francis Group, LLC.